U.S. Foreign Policy in the Middle East: Strategic Goals, Oil Interests, and the Promotion of Democracy - Zazai, Abuzar Khpalwak; Jamili, Fawad (Journal of Progressive Law and Legal Studies, 2025)
This research explores the historical and contemporary role of U.S. intervention in the Middle East, with a particular focus on oil interests, political strategies, and regional stability. The study examines key agreements like the "fifty-fifty" profit-sharing deal in Saudi Arabia and the broader implications of U.S. involvement in Gulf politics. The strategic importance of oil to U.S. national security is a central theme, illustrating how energy concerns have shaped U.S. foreign policy in the region. A significant portion of the research delves into the tension between promoting democracy and securing U.S. strategic interests, highlighting the challenges faced in balancing these often conflicting goals. Methodologically, the research utilizes both quantitative and qualitative approaches, drawing on historical documents, diplomatic records, and contemporary analyses. The findings suggest that while the U.S. has made efforts to foster democratic reforms in the region, its interventions—such as the Iraq invasion—have often resulted in instability, sectarian violence, and the resurgence of authoritarian regimes. The research argues that the U.S. has maintained a strong presence in the Middle East primarily to safeguard its economic and security interests, understanding that the region is vital to both its energy supply and broader geopolitical strategy. The conclusion underscores that U.S. involvement in the Middle East will likely continue in the future, driven by the desire to secure energy resources, maintain regional influence, and counter rivals like Iran, China, and Russia. The research suggests that while U.S. efforts to promote democracy have been largely unsuccessful, its strategic interests will remain dominant in shaping its regional policies.